Simplexviruses Successfully Adapt to Their Host by Fine-Tuning Immune Responses. (22nd June 2022) - Mozzi, Alessandra; Cagliani, Rachele; Pontremoli, Chiara; Forni, Diego; Saulle, Irma; Saresella, Marina; Pozzoli, Uberto; Cappelletti, Gioia; Vantaggiato, Chiara; Clerici, Mario; Biasin, Mara; Sironi, Manuela
Abstract: Primate herpes simplex viruses are species-specific and relatively harmless to their natural hosts. However, cross-species transmission is often associated with severe disease, as exemplified by the virulence of macacine herpesvirus 1 (B virus) in humans. We performed a genome-wide scan for signals of adaptation of simplexviruses to their hominin hosts. Among core genes, we found evidence of episodic positive selection in three glycoproteins, with several selected sites located in antigenic determinants. Positively selected noncore genes were found to be involved in different immune-escape mechanisms. The herpes simplex virus (HSV)-1/HSV-2 encoded product (ICP47) of one of these genes is known to down-modulate major histocompatibility complex class I expression. This feature is not shared with B virus, which instead up-regulates Human Leukocyte Antigen (HLA)-G, an immunomodulatory molecule. By in vitro expression of different ICP47 mutants, we functionally characterized the selection signals. Results indicated that the selected sites do not represent the sole determinants of binding to the transporter associated with antigen processing (TAP). Conversely, the amino acid status at these sites was sufficient to determine HLA-G up-regulation. In fact, both HSV-1 and HSV-2 ICP47 induced HLA-G when mutated to recapitulate residues in B virus, whereas the mutated version of B virus ICP47 failed to determine HLA-G expression. These differences might contribute to the severity of B virus infection in humans. Importantly, they indicate that the evolution of ICP47 in HSV-1/HSV-2 led to the loss of an immunosuppressive effect. Thus, related simplexviruses finely tune the balance between immunosuppressive and immunostimulatory pathways to promote successful co-existence with their primate hosts.